Epidemiology: concepts and diagnosis of diabetes mellitus. - Duarte, R S (1989)
A review is presented of present concepts about diabetes mellitus and the several etiopathogenic mechanisms. Diagnostic criteria and classification are summarised. Some epidemiological data and their implications on prevention are reviewed.